2014
DOI: 10.1038/bjc.2013.808
|View full text |Cite
|
Sign up to set email alerts
|

Jumonji domain-containing protein 2B silencing induces DNA damage response via STAT3 pathway in colorectal cancer

Abstract: Background:Jumonji domain-containing protein 2B (JMJD2B), directly targeted by hypoxia-inducible factor 1α, maintains the histone methylation balance important for the transcriptional activation of many oncogenes. Jumonji domain-containing protein 2B has been implicated in colorectal cancer (CRC) progression; however, the mechanism remains unclear.Methods:Immunofluorescence and western blotting detected phosphorylated histone H2AX, characteristic of double-strand breaks, and comet assay was used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
(72 reference statements)
0
26
1
Order By: Relevance
“…Several reports have shown that STAT3 modulates the DNA damage response pathway (32,38,39). Accordingly, inhibition of activated STAT3 decreases DNA repair activity after IR (40,41). In this study, we demonstrated that the expression of gH2AX, which is an indicator of double-strand DNA breaks after IR, is enhanced in vitro and in vivo after combining radiotherapy with SOCS1 gene therapy, as compared with that with each monotherapy.…”
Section: Discussionmentioning
confidence: 50%
“…Several reports have shown that STAT3 modulates the DNA damage response pathway (32,38,39). Accordingly, inhibition of activated STAT3 decreases DNA repair activity after IR (40,41). In this study, we demonstrated that the expression of gH2AX, which is an indicator of double-strand DNA breaks after IR, is enhanced in vitro and in vivo after combining radiotherapy with SOCS1 gene therapy, as compared with that with each monotherapy.…”
Section: Discussionmentioning
confidence: 50%
“…The epidermal growth factor receptor/STAT3 pathway upregulates the endonuclease, Eme1, to reduce DNA damage after topoisomerase I inhibition (Vigneron et al, 2008). JMJD2B, a hypoxia-inducible factor 1aregulated master regulator of DNA repair genes, which maintains histone methylation balance important for the transcriptional activation of many oncogenes, acts through activating STAT3 (Chen et al, 2014).…”
Section: Genotoxic Stressmentioning
confidence: 99%
“…The current study determined that an increase in H2A.X phosphorylation and a decrease of STAT3 phosphorylation occurred simultaneously when the cells were irradiated with a PB. Chen et al (50) revealed that the inhibition of phosphorylated STAT3 was linked with an increase of H2A.X phosphorylation, indicating DNA damage. Furthermore, Wen et al revealed that apoptosis was enhanced with the phosphorylation of H2A.X by mammalian STE20-like kinase 1 (51).…”
Section: Discussionmentioning
confidence: 99%